Recent attainments of research on plasma physics and technology AT IPJ, Poland - Sadowski, M.J. (Вопросы атомной науки и техники, 2008)
This invited lecture presents the most important achievements of the IPJ team in theoretical- and experimental-studies in the field of plasma physics and technology during recent years. The main efforts concentrated on the development of diagnostic techniques and studies of plasmas in Plasma-Focus (PF) facilities and Multi-Rod Plasma Injectors (RPI). Other efforts concerned diagnostics of fast electrons in selected Tokamaks (CASTOR, ISSTOK, and TORE-SUPRA), fusion protons in TEXTOR, and fusion neutrons in JET (EURATOM). Separate efforts concerned technological applications, e.g. modeling of an IPD accelerator for the material engineering, the use of UHV arc-discharges to deposit superconducting Nb layers on RF cavities and superconducting Pb photo-cathodes in electron injectors (EC CARE).